Pengendalian Suhu dan Kelembaban pada Budidaya Jamur Tiram Berbasis IoT - Helmy Fitriawan; Kholid Ali Dwi Cahyo; Sri Purwiyanti; Syaiful Alam (The University of Lampung, 2020)
Oyster mushrooms (Pleurotus Ostreatus), such as white mushroom, chinese mushroom, and warm mushroom, is one type of edible mushrooms. Oyster mushroom cultivation is usually done at the mushroom house (kumbung) which is mostly made of bamboo. Oyster mushrooms can grow optimally by controlling the temperature and humidity in the kumbung. Kumbung environment conditioning is usually done manually by spraying water on the planting medium every 8 hours. But this is perceived as ineffective and requires high effort. For this reason, we need a technology that can monitor as well as control the environmental conditions inside the kumbung automatically and remotely. This paper describes the design of a system to monitor and control the temperature and humidity in the kumbung for oyster mushroom cultivation based on IoT (Internet of Things). This system is developed consisting of five parts, i.e sensor modules, microcontrollers, data loggers, actuators, and monitoring and control interfaces. The main result of this study is a remote monitoring and control of environmental conditions for oyster mushroom cultivation. The data of monitoring, in the form of temperature and humidity, are saved to the data logger and can be downloaded in the format (.csv). The system works functionally in accordance with the expected specifications, both in terms of sensor readings and actuator controlling.